MEMBANGUN KOLABORASI EFEKTIF: PERAN GAYA KEPEMIMPINAN DALAM TRANSFORMASI INDIVIDU MENUJU TIM BERKINERJA TINGGI - Farrah Dzawi Adila; Sukarman, Sukarman; Arifia Ika Fakhrina; Zaenudin Khabib; Evi Septiana Farida; M. Luqmanul Haqim (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Collaboration is a key element in improving organizational effectiveness and competitiveness. However, an individual's ability to collaborate does not develop spontaneously; rather, it is influenced by leadership styles that direct, motivate, and create a work environment that supports positive interactions. This study aims to illustrate the role of leadership styles in transforming individuals into high-performing teams. Secondary data were collected from relevant scientific articles, academic books, and policy documents, then analyzed thematically to obtain a conceptual and empirical synthesis. The results of the study indicate that transformational and participatory leadership have the most significant influence on the formation of effective collaboration, primarily through increased trust, open communication, and a sense of shared responsibility. These findings confirm that leadership style not only influences individual behavior but also determines the quality of collaboration and overall team performance. Therefore, organizations need to develop more humanistic, adaptive, and inclusive leadership styles to encourage the creation of high-performing teams.